Resistência parcial e fungicidas no controle da ferrugem asiática da soja - Silva, Valdirene Aparecida Stabile (2007)
Soybean asian rust, caused by the fungus Phakopsora pachyrhizi, is one of the major pest problems in the crop. Disease control has required a combination of cultural practices to minimize losses. Among the control methods, chemical control with fungicides, has been the only one available. Control strategies, such as the use of cultivars with partial resistance to the fungus are desirable for an effective disease management in the crop. This study was done to study partial resistance, sowing dates and fungicides for soybean asian rust control, in the field, as part of the search for new cultivars with partial resistance to aid rust control. The experiment was one in Uberlândia-MG, in field conditions, from September 2005 to May 2006 and consisted of two sowing dates. The following variables were evaluated: disease incidence, severity, as the percentage of diseased leaf area, severity, as a visual score of the plot, number of pustules cm-2, weight of one thousand seeds and yield. Based on the variables incidence, both severities, and number of pustules cm-2 the area under the disease progress curve (AUDPC) was calculated. Subsequently, the analysis of variance was done and the averages compared by the Scott-Knott test, at 5% probability. Significant differences were observed among cultivars and treatments, among the values of AUDPC, as well as among the weight of one thousand seeds and yield. Based on the results of this study, cultivars IAC-100, Potenza and UFUS-Impacta, presented the lowest values of AUDPC in both sowing dates, thus demonstrating the presence of partial resistance to soybean asian rust in these genotypes. The fungicide triazol (Cyproconazole) and its mixture with a fungicide strobilurin (Azoxystrobina + Cyproconazole) were effective on the control of soybean asian rust in both sowing dates. Disease was most aggressive in the second sowing date due to the greater inoculum pressure.